Trends and knowledge gaps in field research investigating effects of anthropogenic noise - Jerem, Paul; Mathews, Fiona (Conservation biology, 2021)
Anthropogenic noise is a globally widespread sensory pollutant, recognized as having potentially adverse effects on function, demography, and physiology in wild animals. Human population growth and associated changes in urbanization, transportation, and resource extraction all contribute to anthropogenic noise and are predicted to increase in the coming decades. Wildlife exposure to anthropogenic noise is expected to rise correspondingly. Data collected through field research are uniquely important in advancing understanding of the real‐world repercussions of human activity on wildlife. We, therefore, performed a systematic review of literature published from 2008 to 2018 that reported on field investigations of anthropogenic noise impacts. We evaluated publication metrics (e.g., publication rates and journal type), geographical distribution of studies, study subject, and methods used. Research activity increased markedly over the assessment period. However, there was a pronounced geographical bias in research, with most being conducted in North America or Europe, and a notable focus on terrestrial environments. Fewer than one‐fifth of terrestrial studies were located in rural areas likely to experience urbanization by 2030, meaning data on ecosystems most likely to be affected by future changes are not being gathered. There was also bias in the taxonomic groups investigated. Most research was conducted on birds and aquatic mammals, whereas terrestrial mammals, reptiles, amphibians, fish, and invertebrates received limited attention. Almost all terrestrial studies examined diurnal species, despite evidence that nocturnality is the prevailing animal activity pattern. Nearly half the studies investigated effects of road or urban noise; the bulk of research was restricted to functional, rather than physiological or demographic consequences. Few experimental studies addressed repercussions of long‐term exposure to anthropogenic noise or long‐term postexposure effects, and multiple noise types or levels were rarely compared. Tackling these knowledge gaps will be vital for successful management of the effects of increasing wildlife exposure to anthropogenic noise. Tendencias y Vacíos de Conocimiento en el Trabajo de Campo que Investiga los Efectos del Ruido Antropogénico Resumen El ruido antropogénico es un contaminante sensorial con amplia distribución global. Se le reconoce como un contaminante con efectos adversos potenciales sobre la función, demografía y fisiología de la fauna silvestre. El crecimiento de las poblaciones humanas y los cambios asociados a la urbanización, transporte y extracción de recursos contribuyen al ruido antropogénico y se pronostica que todos incrementarán en las siguientes décadas. Se espera que la exposición de la fauna al ruido antropogénico aumente en correspondencia. Los datos recolectados por medio del trabajo de campo tienen una importancia única en el avance del entendimiento de las repercusiones reales de la actividad humana en la fauna. Por lo tanto realizamos una revisión sistémica de la literatura publicada de 2008 a 2018 en la que se reportaron investigaciones en campo de los impactos del ruido antropogénico. Evaluamos las medidas de publicación (p. ej.: las tasas de publicación y el tipo de revista), la distribución geográfica de los estudios, el sujeto del estudio y los métodos que se utilizaron. La actividad de investigación aumentó de manera marcada a lo largo del periodo de evaluación. Sin embargo, hubo un sesgo geográfico pronunciado en las investigaciones pues la mayoría se realizó en América del Norte o en Europa y hubo un enfoque notable sobre los ambientes terrestres. Menos de la quinta parte de los estudios terrestres estuvieron ubicados en áreas rurales con una probabilidad de sufrir urbanización para el 2030, lo que significa que no se están recopilando datos para los ecosistemas con mayor probabilidad de ser afectados en el futuro. También hubo un sesgo en los grupos taxonómicos investigados. La mayoría de las investigaciones se realizó en aves y en mamíferos acuáticos, mientras que los mamíferos terrestres, los reptiles, los anfibios, los peces y los invertebrados recibieron una atención limitada. Casi todos los estudios terrestres trabajaron con especies diurnas, a pesar de la evidencia existente de que los hábitos nocturnos son el patrón prevaleciente de actividad animal. Casi la mitad de los estudios investigaron los efectos del ruido urbano o de las carreteras; el grueso de las investigaciones estuvo restringido a las consecuencias funcionales y no tanto a las fisiológicas o demográficas. Pocos estudios experimentales trataron el tema de las repercusiones a largo plazo de la exposición al ruido antropogénico o el de los efectos post‐exposición a largo plazo. Tampoco encontramos muchos estudios en los que se compararan los tipos o niveles de ruido. Será vital lidiar con estos vacíos de conocimiento para el manejo exitoso de los efectos de la creciente exposición de la fauna al ruido antropogénico. 摘要 人为噪音是一种全球广泛存在的感官污染, 它被认为对野生动物的功能、种群和生理都有潜在的负面影响。人口增长以及城市化、交通和资源开采等方面的相关变化都会制造人为噪音, 且预计在未来几十年还会增加。相应地, 野生动物接触人为噪音的机会也预计会增加。通过实地研究收集的数据对于进一步了解人类活动对野生动物的实际影响具有独特的重要意义。因此, 我们对 2008 年至 2018 年发表的关于人为噪音影响的实地调查的文献进行了系统综述。我们评估了发表指标 (如发表率和期刊类型) 、研究的地理分布、研究主题和使用的方法。在我们评估涵盖的时间段内, 研究活动有显著增加。然而, 研究存在明显的地理偏向, 大多数在北美或欧洲进行, 且明显聚焦于陆地环境。陆地环境的研究中只有不到五分之一位于可能在2030年前发生城市化的农村地区, 这意味着最有可能受到未来变化影响的生态系统的数据没有得到收集。我们发现, 调查研究的类群也存在偏向性, 大多数研究是在鸟类和水生哺乳动物中进行的, 而陆生哺乳动物、爬行动物、两栖动物、鱼类和无脊椎动物得到的关注有限。尽管有证据表明动物主要的活动模式是夜间活动, 然而几乎所有陆地环境的研究只调查了昼间活动物种。近一半的研究调查了道路或城市噪音的影响;大量研究仅限于功能性影响, 而非生理或种群方面的影响。很少有研究通过实验探讨长期暴露于人为噪音中的影响或是长期暴露后产生的效应, 也很少有研究对多种噪音类型或水平进行比较。弥补这些知识空缺对于成功管理不断加剧的野生动物暴露于人为噪音的影响至关重要。【翻译: 胡怡思; 审校: 聂永刚】 Article Impact Statement: Future field research into effects of noise pollution on wildlife must focus on underrepresented ecosystems, taxa, and activity patterns.